Evaluation of Growth and Carcass Characteristics of Broiler Chickens (Cobb 500) Feed on Different Level of Organic Acids Inclusion in Diet at Parwanipur - Jha, A. K.; Azad, Md. H.; Ali, Md.S. N.; Alam, P.; Sheikh, N.; Ali, H.; Ansari, K. (Nepalese Veterinary Journal, 2019)
An experiment was carried out to evaluate the effect of different level of organic acids on productive traits, carcass yields and body parts (Thigh, Back, Neck, wings and Breast) of broiler chicken. This experiment was conducted at Regional Agricultural Research Station, Parwanipur, Bara for 41 days to test the effect of organic acids inclusion in broiler feed and its effect on growth performance and carcass study. Altogether 225 day old Cobb-500 broiler birds were procured from Shivam Hatchery, Birgung and divided into 5 treatments with 3 replications (15 birds in each replication) by using completely randomized design. Concentrate feed was purchased from Posak Feed industry, Birgung. Control group (T1) was feed without organic acid inclusion and whereas T2, T3, T4 and T5 groups were fed concentrate mixture mixed with different combination of organic acids @ 400ml/ per 100 kg feed, respectively. Experimental birds were provided adlib amount of grower feed (B1) for 21 days and that after finisher feed (B3) for 20 days and had easily access to drinking water. Feed intake was recorded daily and body weight gain was measured in 7 days interval. Experiment revealed that highest weight gain was observed in T2 (2.6 kg) followed by T3 (2.5) where combination of organic acids were formic acid 65% + propionic acid 35% and formic acid 65% and citric acid 35%, respectively, however, it was not significant among diet groups. From every treatment group each birds were selected for carcass and body parts study. The study showed significant difference (P<0.5) in carcass quantity and body parts of the birds between the treatment groups. The dressing percentage of T1, T2, T3, T4 and T5 were 68.96%, 67.87%, 70.38%, 69.88% and 69.67% respectively. Experiment suggested that further study should be carried out to precise the appropriate level of organic acids inclusion and higher cost benefit ratio.